PENGGUNAAN FUNGSI PELENGKAP PADA KALIMAT DALAM TRACT MEI 1968 - Tamba, Nokiamy Sesena; Laksman-Huntley, Myrna (Universitas Hasanuddin, 2020)
Tract as a communication platform to call people to participate in demonstrations is still used by the French until 2019 in the Yellow Vest Movement. This proves the important usage of the track in France. The most important movement in French history that involves the utilization of tract was in Mai 68. By using it, the movement initiated by students of the University of Nanterre (May, 3rd 1968) was able to invite workers to join them on May 13 1968. However, it has a disadvantage due to paper usage: spatial limitations for the transmission of information. Therefore, it is necessary to pay attention to the choice of words, phrases, clauses, sentences, and presentations. Use qualitative methods and literature study; this article describes the utilization of the function accessory in the tracts on May 13 68, based on the sentence structure theory by Le Querler (1994). In the tract, variations of function accessories are presented according to the amount of paper used and to the freedom of presentation of the sentence by the creator. As a result, its utilization and presentation in the tract help the various groups involved on May 13, 1968, to gain a better understanding of the reasons and objectives to be carried out in the movement.